Outcomes of Patients on Maintenance Hemodialysis Admitted to a Tertiary Care Hospital with COVID-19 - Mudassar Murtaza Cheema , Zein El Amir , Zeeshan Qadeer ,Ahmed Trimzi (Journal of Rawalpindi Medical College, 2021)
Background: The coronavirus disease-2019 pandemic has caused a disastrous world health crisis. The patients with renal disease, particularly those who are receiving regular dialysis therapy have elevated risk of COVID-19 infection-associated complications as well as poor prognosis including enhanced risk of hospital admission, mechanical ventilation and mortality. Objective: The objective of the study is to assess the outcomes of patients on maintenance dialysis admitted to a tertiary care hospital with COVID-19. Material and Methods: This retrospective study was performed in a Tertiary Care Hospital from March 2020 to August 2020. A total of 44 patients were included in the study. Data collected through questionnaire was analyzed using the computer software SPSS 24.0. Frequencies and percentages were calculated for categorical data while mean+SD was calculated for quantitative data. Results: Among 44 patients, 63.6% were males and the mean age was 46.86+12.413 years. Mean number of dialysis were 3.57+2.214. The mean ferritin level was 2067.05+788.412 ng/ml and mean C-reactive protein level was 111.59+32.998 mg/L. Among these patients, 65.9% were discharged and 34.1% patients expired. Conclusion: Study concluded that elevated levels of inflammatory markers such as ferritin and CRP are found among patients on maintenance dialysis with COVID-19.